Expression in Bacillus subtilis of the Bacillus thuringiensis cryIIIA toxin gene is not dependent on a sporulation-specific sigma factor and is increased in a spo0A mutant. - Agaisse, H (1994)
Expression of the Bacillus thuringiensis cryIIIA gene encoding a Coleoptera-specific toxin is weak during vegetative growth and is activated at the onset of the stationary phase. cryIIIA'-'lacZ fusions and primer extension analysis show that the regulation of cryIIIA expression is similar in Bacillus subtilis and in B. thuringiensis. Activation of cryIIIA expression was not altered in B. subtilis mutant strains deficient for the sigma H and sigma E sporulation-specific sigma factors or for minor sigma factors such as sigma B, sigma D, or sigma L. This result and the nucleotide sequence of the -35 and -10 regions of the cryIIIA promoter suggest that cryIIIA expression might be directed by the E sigma A form of RNA polymerase. Expression of the cryIIIA'-'lacZ fusion is shut off after t2 (2 h after time zero) of sporulation in the B. subtilis wild-type strain grown on nutrient broth sporulation medium. However, no decrease in cryIIIA-directed beta-galactosidase activity occurred in sigma H, kinA, or spo0A mutant strains. Moreover, beta-galactosidase activity was higher and remained elevated after t2 in the spo0A mutant strain. beta-Galactosidase activity was weak in abrB and spo0A abrB mutant strains, suggesting that AbrB is responsible for the higher level of cryIIIA expression observed in a spo0A mutant. However, both in spo0A and spo0A abrB mutant strains, beta-galactosidase activity remained elevated after t2, suggesting that even in the absence of AbrB, cryIIIA expression is controlled through modulation of the phosphorylated form of Spo0A. When the cryIIIA gene is expressed in a B. subtilis spo0A mutant strain or in the 168 wild-type strain, large amounts of toxins are produced and accumulate to form a flat rectangular crystal characteristic of the coleopteran-specific B. thuringiensis strains.